Modifications of EEG power spectra in mesial temporal lobe during n-back tasks of increasing difficulty. A sLORETA study - Imperatori, Claudio; Farina, Benedetto; Brunetti, Riccardo; Gnoni, Valentina; Testani, Elisa; Quintiliani, Isabella; Del Gatto, Claudia; Indraccolo, Allegra; Contardi, Anna; Speranza, Anna Maria; Della Marca, Giacomo (Frontiers in Human Neuroscience, 2013)
The n-back task is widely used to investigate the neural basis of Working Memory (WM) processes. The principal aim of this study was to explore and compare the EEG power spectra during two n-back tests with different levels of difficulty (1-back vs 3-back). Fourteen healthy subjects were enrolled (7 men and 7 women, mean age 31.21±7.05 years, range: 23-48). EEG was recorded while performing the N-back test, by means of 19 surface electrodes referred to joint mastoids. EEG analysis were conducted by means of the standardized LOw Resolution brain Electric Tomography (sLORETA) software. The statistical comparison between EEG power spectra in the two conditions was performed using paired t-statistics on the coherence values after Fisher’s z transformation available in the LORETA program package. The frequency bands considered were: delta (0.5-4 Hz); theta (4.5–7.5 Hz); alpha (8–12.5 Hz); beta (13–30 Hz); gamma (30.5–100 Hz). Significant changes occurred in the delta band: in the 3-back condition an increased delta power was localized in a brain region corresponding to the Brodmann Area (BA) 28 in the left posterior entorhinal cortex (T = 3.112; p<0.05) and in the BA 35 in the left peririnhal cortex in the parahippocampal gyrus (T = 2.876; p<0.05). No significant differences were observed in the right hemisphere and in the alpha, theta, beta and gamma frequency bands. Our results indicate that the most prominent modification induced by the increased complexity of the task occur in the mesial left temporal lobe structures.